2016
DOI: 10.1038/srep29265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the environment on the secondary metabolic profile of Tithonia diversifolia: a model for environmental metabolomics of plants

Abstract: Tithonia diversifolia is an invasive weed commonly found in tropical ecosystems. In this work, we investigate the influence of different abiotic environmental factors on the plant’s metabolite profile by multivariate statistical analyses of spectral data deduced by UHPLC-DAD-ESI-HRMS and NMR methods. Different plant part samples of T. diversifolia which included leaves, stems, roots, and inflorescences were collected from two Brazilian states throughout a 24-month period, along with the corresponding monthly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
210
2
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(259 citation statements)
references
References 55 publications
8
210
2
14
Order By: Relevance
“…Table 1 showed yield and density of essential oil of A. spinosa collected in different time. The result obtained showed the amount of essential oil produced by the plant can be modified by external factors such as climate and internal like plant phenology 30 . The general yield of these specie is low compared with reports for A. trifurcata and A. cryptanta from San Juan, Argentina, described previously others authors where it is reported composition of essential oil in the range of 21 to 0.2 % 23, 24 , however our analysis showed yield of 12 to 0.03%.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Table 1 showed yield and density of essential oil of A. spinosa collected in different time. The result obtained showed the amount of essential oil produced by the plant can be modified by external factors such as climate and internal like plant phenology 30 . The general yield of these specie is low compared with reports for A. trifurcata and A. cryptanta from San Juan, Argentina, described previously others authors where it is reported composition of essential oil in the range of 21 to 0.2 % 23, 24 , however our analysis showed yield of 12 to 0.03%.…”
Section: Resultsmentioning
confidence: 91%
“…The results obtained suggest that the contituents are principally the same for three collections studied, with any differences in minor constituents. In general the genus Azorella grows in poor soils, which could indicate that these plant components serve as protection against desiccation, high solar radiation and unfavorable weather and geographical conditions due to highly specialized physiological processes that affect their chemical response 30 . These reach from the synthesis of special lipids that modify cell membranes for flexibility and H 2 O permeability to other features like the cushion-growth form of A. spinosa as a way of reducing extreme temperatures and H 2 O fluctuations, process not seen in low-altitude plants 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The production and accumulation of primary and secondary metabolites by plants is greatly affected by the environmental factors. Moreover, secondary metabolites biosynthesis by plants is the result of chemical interaction between plants and their environment, and variations in the plant metabolic profiles seem to be a direct response to changes in conditions of the plant surrounding environment (Sampaio et al, 2016). Therefore, the difference in environmental conditions could account for variation in the metabolic profile of the same plant species collected from different geographical locations.…”
Section: Escherichia Coli Pseudomonas Aurigenosa Staphylococcus Aurmentioning
confidence: 99%
“…These metabolites mostly belong to the class of sesquiterpene lactones, flavonoids and trans-cinnamic-acid derivatives (mainly caffeoylquinic acid) and possess several therapeutic properties (Sampaio ., 2016). The gaseous as well as heavy-metal pollutants are markedly hazardous when in high concentration.…”
Section: Thevetia Neriifolia Et Almentioning
confidence: 99%